Primary ewing's sarcoma of the lumbosacral spine : a case report - Zakaria@Mohamad, Zamzuri; Ayeop, Mohd Adham Shah; Awang, Mohamed Saufi; Abd. Aziz, Azian; M, Fadhli (Faculty of Medicine, International Islamic University Malaysia, 2012)
Ewing's sarcoma is a rare tumor first discovered by James Ewing in 1921. It is more common in bone or skeletal component compared to soft tissue or extraosseous Ewing's sarcoma. Among soft tissue Ewing's, spinal cord involvement is rarer with only nine cases reported. We report a case of nine-year-old Malay girl who presented with low back pain for two months following a fall with progressive neurological deficits of bilateral lower limb. Magnetic resonance imaging was suggestive of a well-defined margin of intradural extramedullary tumor. With nerve sheath tumor in mind, surgical excision with laminectomy L2-S1 was performed. Intraoperative finding was an extradural mass from L3-L5 with extension to bilateral neuroforamen. Histopathology report defined a round cell tumour of Ewing's sarcoma from the mass.